PEREMPUAN DAN POLITIK DARI PEMILU KE PEMILU : Mengawal Keterwakilan Perempuan Melalui Affirmative Action - Ari Pradhanawati (Faculty of Law, Universitas Diponegoro, 2010)
Woman political map election by election can only be guided through 30 % woman representative and must be applied with affirmative action. Since it thought that the policy only provide advantages to woman and not all the political parties have gender sensitivity Descriptive analysis is the method to analyse woman's vote mapping according to general election report in 1999, 2004, and 2009. One of theory applied to observe voter behaviour in mapping vote stated by Adman Nursaf refers to some Columbia and michigan tradition (psycological approach )and rational approach. Analysis report, most voted women who are success in gaining support and position in House of Representative have been increased compared to general election in 1999 and 2004. However, woman representation in House of Representative has not reached to 30% minimum quota yet. That is the reason why woman's qouta must be fighting for through legals. Considering the legal in quota domain is part of affirmative policy along with a hope, there is gonna be equality and balance between man and woman in House of Representative until it could be overcome